Kawasaki Disease and Aneurysm of Coronary Artery in Children - Djalilah, Gina Noor; Airlangga , Muhammad Perdana; kartikasari, irma; Rahman , Mahrus A; Utamayasa, I Ketut Alit; Ontoseno , Teddy (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2025)
Kawasaki infection (KD) is an intense, self-restricted vasculitis of obscure etiology that occurs predominantly in babies and small children. KD is a disease of youth, as 80% of cases happen between the ages of half a year and 5 years, with a median age of 2 to 3 years. Males are 1-6 times more likely to be influenced by KD. The ailment influences offspring of all ethnic groups, with the highest frequency occurring in offspring of Asian descent. A 3-year-old kid, with fever for 11 days before the diagnosis. Fever continues to spike. The patient got treated with anti-toxins before, yet the fever won’t resolve. His eyes look red on the third day of fever. Fever followed by redness in the entire body that began from crotch to trunk, vanished in 7 days of fever, redness, enlarged in hands and feet, additionally lymph hub broadening in neck with width 1.5 cm, non-purulent, the lips was red and strawberry tongue show up in 6 days of fever and pilling skin while redness in hands and feet settled. Research facility assessment discovered an increase in leucocytes, ESR, and CRP, and a normal Electrocardiogram (ECG). Echocardiography revealed an aneurysm right coronary artery and an aneurysm of the left coronary artery. The board of patients incorporates intravenous gamma globulin, ibuprofen for therapy, echocardiography assessment, and therapy support. Long-term follow-up overseeing Kawasaki disease is the way to screen Coronary Arterial Aneurysm (CAA) complications, which are the most serious complications of KD, and are a significant reason for morbidity and mortality associated with the infection.